The flying carpet - Hunt, Roderick (China: Oxford university press, 2012)
Suitable for consolidation and reading practice with groups or individuals. This title aims to teach the conventions of drama, and develop skills in reading aloud and shared reading. Each play has a cast list of between four and six characters, including one or more narrators. There are six lines of text per page and suggestions for sound effects.
Keywords: English reader